Membangun Kerukunan Antar Umat Beragama : Belajar dari Desa Balun, Kabupaten Lamongan - Galang Setia Abadi; Asrofatul Azizah (Universitas Islam Darul Ulum Lamongan, 2020)
Indonesian society has local cultures and traditions that are functionally able to maintain the environment situation in order to remain harmonious, both with fellow humans and the environment. These local traditions have important meanings and values, among others, as a reference for the behavior of the people in living their lives, including dealing with differences in interacting with other people with different cultures. These local traditions are actually the expression of local knowledge or local wisdom of a community in responding to their environmental situation. Balun Community Balun Village Balun District Lamongan Regency is able to maintain religious harmony, even though they have different religions. This is due to the existence of elements which become social glue in the form of local wisdoms that live in Balun society. Substantially, local wisdom is the values ​​that apply in a society. These values ​​are believed to be true and become a reference in the daily behavior of the local community. These local wisdom values ​​are seen as entities that determine dignity and human dignity in the community because it contains elements of creative intelligence and local knowledge from the elite and the community. Research conducted with this qualitative approach reveals local wisdom in the Balun community in maintaining harmony in the form of traditional expressions and festivity. The Balun community has a harmonious social outlook expressed through various traditional expressions such as the pillars of agawe santosa crah agawe bubrah.